Estudios Visuales e Intermedialidad: el caso del videojuego Assassin’s Creed Unity (Ubisoft, 2014) - Piñol-Lloret, Marta (Eikón / Imago, 2024)
Nowadays, images are everywhere: we are surrounded by them, we live by them, we inhabit them and we even become images. That is why it is imperative to approach Art History with an inclusive approach that allows us to rethink its roles and add new media, among which videogames stand out. Therefore, we have drawn its analysis from Visual Studies and we have questioned ourselves about the intermediality and transmediality of one of the games of the Assassin’s Creed saga, Unity (Ubisoft, 2014), especially relevant to approach technoculture, the materialization of space in a place and how it is deployed in videogames, the strategies developed by this title to appeal to authenticity by relying on verisimilitude and recognition instead of accuracy, the relevance of anachronism, how it explores the connections between history and memory, and how it is situated in relation to genres. As evidenced in the article, videogames address all these issues and acknowledge the weight of our visual memory and the role it plays in how we perceive images and the importance we give to them.